Evaluation of friction welded dissimilar pipe joints between AISI 4140 and ASTM A 106 Grade B steels used in deep exploration drilling. (August 2020) - Sk., Abdul Khadeer; P., Ramesh Babu; B., Ravi Kumar; A., Seshu Kumar
Abstract: In the present research work, a detailed evaluation of dissimilar friction welded joints between the hot rolled ASTM A106 Grade B (carbon steel) pipes and hot rolled AISI 4140 (low alloy steel) pipes in the as-received (AR) condition and quenched and tempered (QT) condition has been carried out. All the specimens were subjected to stress relief annealing after welding. Optical and scanning electron microscopy on the AISI 4140 steel side revealed dynamically recrystallized grains, consisting of a mixture of ferrite and martensite in the friction welded AR-condition joints and mixture of ferrite and tempered martensite in the friction welded QT-condition joints. On the ASTM A 106 Grade B steel side the material showed ferrite and pearlite microstructure. SEM analysis did not reveal any intermixing between AISI 4140 and ASTM A106 Grade B steels at the weld interface in both the conditions. The region adjacent to the weld interface on AISI 4140 steel side consistently showed higher hardness in the QT-condition compared to AR-condition due to the presence of fine-grained microstructure in QT-condition. The dissimilar welded pipe joints in the present study have shown slightly higher tensile properties than that of ASTM A106 Grade B steel but significantly lower than that of AISI 4140 steel. The friction welded dissimilar pipe joint specimens have shown substantially lower impact toughness values compared to either ASTM A 106 Grade B steel or AISI 4140 steel in both AR and QT-conditions due to the presence of carbides at the weld interface.